2022
DOI: 10.1088/1748-9326/ac5bb4
|View full text |Cite
|
Sign up to set email alerts
|

Fisheries yields and species declines in coral reefs

Abstract: Negative trade-offs between food production and biodiversity and the positive functional diversity - productivity relationships are potentially conflicting paradigms that are frequently evoked in conservation and sustainability science and management. While the complementary niches of species could potentially increase fisheries yields, stark food-diversity trade-offs have been proposed for wild-caught fisheries. Nevertheless, this first evaluation of stock biomass, yields, and species relationships in 115 cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…The low production findings contrast with previous production estimates using a similar space‐for‐time substitution method and more widely distributed WIO data from more fisheries closures. The study concluded that fishable and target fish production in the WIO province had an r of ~0.23 (McClanahan, 2022). Many reef closures in the broadscale compilation were in more ocean‐exposed environments compared to reefs leeward of the large Pemba and Zanzibar islands in this more site restricted compilation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The low production findings contrast with previous production estimates using a similar space‐for‐time substitution method and more widely distributed WIO data from more fisheries closures. The study concluded that fishable and target fish production in the WIO province had an r of ~0.23 (McClanahan, 2022). Many reef closures in the broadscale compilation were in more ocean‐exposed environments compared to reefs leeward of the large Pemba and Zanzibar islands in this more site restricted compilation.…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale studies suggest a series of ecological thresholds associated with fish biomass that will have consequences for ecological processes, such as fisheries production and reef growth (McClanahan, Graham, et al, 2011). Thresholds vary along fisheries production gradients but many including biodiversity are supported at or just above maximum sustained yield (MSY) fisheries levels (McClanahan, 2018a(McClanahan, , 2022. What is less understood is the variability in fisheries production rates and the differences between existing and optimal catch rates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, their management is complex due to its characteristics of multiple gears, multi-species, many resource users, seasonality, and presence of migrant shers, thus rendering traditional sheries management hard to implement or ineffective (Munga et al, 2014). These complexities are related to the challenges that local management presents around the use of illegal gear, increasing number of shers and increasing demand for sh which compromise conservation efforts (Galligan et al, 2022;Mangi et al, 2007;McClanahan, 2022).…”
Section: Filling the Missing Link: Practices Local Categories And Cla...mentioning
confidence: 99%